2020
DOI: 10.3390/agronomy10091413
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Pollination Services Provided by Wild and Managed Bees (Apoidea) in Wild Blueberry (Vaccinium angustifolium Aiton) Production in Maine, USA, with a Literature Review

Abstract: Maine is the largest producer of wild blueberry (Vaccinium angustifolium Aiton) in the United States. Pollination comes from combinations of honey bees (Apis mellifera (L.)), commercial bumble bees (Bombus impatiens Cresson), and wild bees. This study addresses (1) previous research addressing wild-blueberry pollination, (2) effects of wild-bee and honey-bee activity densities on fruit set, yield, and crop value, (3) the economic value of wild-bee communities, and (4) economic consequences of pollinator loss. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 84 publications
1
9
0
Order By: Relevance
“…Our finding is in line with existing studies that have found that intensive farming practices in general, not only chemical usage, contribute to lower pollinator diversity, particularly in tropical environments [11,[56][57][58][59]. High pollinator diversity has been shown to improve crop productivity in smallholder farms, increase coffee fruit set and improve the amount and frequency of pollination services [50,[60][61][62]. Consequently, preserving pollinator diversity is essential if we are to address global food insecurities, reverse global pollinator decline and re-establish degraded ecosystem service provision [2,63].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our finding is in line with existing studies that have found that intensive farming practices in general, not only chemical usage, contribute to lower pollinator diversity, particularly in tropical environments [11,[56][57][58][59]. High pollinator diversity has been shown to improve crop productivity in smallholder farms, increase coffee fruit set and improve the amount and frequency of pollination services [50,[60][61][62]. Consequently, preserving pollinator diversity is essential if we are to address global food insecurities, reverse global pollinator decline and re-establish degraded ecosystem service provision [2,63].…”
Section: Discussionsupporting
confidence: 91%
“…In our case, and in the case of the Pywell et al [72] study, farmers use a system of land-sharing (i.e., agroforestry), as opposed to land-sparing which intensifies farming in one area whilst sparing other areas for entirely conservation purposes [73]. It could be extrapolated that for areas in which land-sharing is not an option, crop yields may suffer as a result of implementing wildlife-friendly practices to preserve pollination services, such as what is observed in Hardman et al's [62] study. However, whilst crop yields may decline as a result of implementing wildlife-friendly farming practices in few cases, it could be argued that this effect is diminished due to increased pollinator diversity and complementarity providing greater ecosystem resilience and thus, greater security with regard to food production and farmer income [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Wild blueberry is an obligate insect-pollinated plant, mostly dependent upon bees [5,40]. Migratory honey bee hives are heavily used to supplement or replace the pollination service by native bee species [5,41]. There has been concern by both honey beekeepers and wild blueberry growers about the health of colonies that are brought in for pollination services each year.…”
Section: Discussionmentioning
confidence: 99%
“…For watermelon crops, as native solitary bees are effective pollinators but do not allow optimal yield, supplementary pollination services through A. mellifera are suggested, even if in this case native managed stingless bees are preferable because they compete less with native pollinators [ 46 ]. In wild blueberry, both honey bee and bumblebee abundance increases fruit set and reduces spatial heterogeneity in crop production [ 47 ].…”
Section: Regulating Services: the Conservation Of Plant Biodiversity ...mentioning
confidence: 99%